Hi, Let's Meet Online! A Study of Virtual Meeting Platforms During the Pandemic - Lim, Liew Xing; Lim, Pei En; Lim, Shin Hui; Lim, Yan Xu; Oktaviandra, Alifia Galuh (AIBPM Publisher, 2022)
In this era of globalization, technological developments are becoming more sophisticated and connecting people worldwide. Technology advancement is essential, and its importance can be seen especially during the Covid-19 pandemic. Virtual meeting platforms have become the main platform to strengthen people's connections from different places. People held more meetings using virtual meetings platforms throughout the current global pandemic. The shifting from face-to-face to online meetings has related to some challenges, prompting questions about how meetings using virtual online platforms may contribute to users' satisfaction. This study focuses on users' intention to use virtual meeting platforms for work-related meetings or education-related lectures during the Covid-19 pandemic.Â The researchers found that perceived usefulness, convenience, and risk are strongly associated with user intention to use virtual meeting platforms. This study adds new insights into the literature related to virtual meeting platforms.